Analysing influence of shareholder decision on green innovation knowledge sharing by fuzzy set qualitative comparative analysis combined evolutionary game theory - Wang, Zhenqing; Yang, Yuqi (Frontiers in Energy Research, 2023)
The background of mixed ownership reform provides policy support and institutional guarantee for the sharing of green innovation knowledge among state-owned capital, non-public capital, and collective capital, which to some extent facilitates the exchange and flow of green innovation knowledge among different enterprises. Based on the perspective of knowledge flow, this article proposes a fuzzy set qualitative comparative analysis game framework and verifies its rationality with real data from energy enterprises, makes reasonable assumptions about the sharing of green innovation knowledge between state-owned and non-state-owned shareholders under mixed reform and uses evolutionary game theory to construct an evolutionary game model for the sharing of green innovation knowledge between both parties. This article studies and explores the evolution and local stability of green innovation knowledge sharing decisions between state-owned and non-state-owned shareholders. Furthermore, numerical simulation methods were used to numerically simulate and analyze the relevant factors affecting green innovation knowledge sharing. Then, fuzzy set Qualitative Comparative Analysis (fsQCA) was used to reveal the multi condition combination influence path that affects green innovation knowledge sharing in enterprises from a configuration perspective. Research has shown that: (1) The choice of green innovation knowledge sharing strategies by state-owned and non-state-owned shareholders largely depends on the difference between the benefits brought by knowledge sharing and the costs of knowledge sharing. Only when the benefits of knowledge sharing exceed the costs incurred by knowledge sharing, may the outcome of the game be stable when both parties adopt knowledge sharing strategies. (2) Improving the coefficient of collaborative benefits, knowledge stock level, and knowledge sharing incentive level, while reducing the cost of knowledge sharing, can promote different capital to choose knowledge sharing strategies. (3) Government led, government enterprise driven, and enterprise led are the three major influencing paths for promoting green innovation knowledge sharing.